Learning Tableau 2022 : create effective data visualizations, build interactive visual analytics, and transform your organization - Milligan, Joshua N.; Hutchinson, Blair; Tossell, Mark; Andreoli, Roberto (Expert insight., 2023)
This edition of Learning Tableau will empower you to bring data to life and make better business decisions. About This Audiobook Learn the basics of data analysis, from snappy visualizations to comprehensive dashboards Gain meaningful insights with geospatial analysis, scripting extensions, and other advanced methods Explore the latest Tableau 2022 features, including Einstein Discovery and Explain Data In Detail Learning Tableau 2022 helps you get started with Tableau and data visualization, but it does more than just cover the basic principles. It helps you understand how to analyze and communicate data visually, and articulate data stories using advanced features. This new edition is updated with Tableau's latest features, such as dashboard extensions, Explain Data, and integration with CRM Analytics (Einstein Analytics), which will help you harness the full potential of artificial intelligence (AI) and predictive modeling in Tableau. After an exploration of the core principles, this audiobook will teach you how to use table and level of detail calculations to extend and alter default visualizations, build interactive dashboards, and master the art of telling stories with data. You'll learn about visual statistical analytics and create different types of static and animated visualizations and dashboards for rich user experiences. We then move on to interlinking different data sources with Tableau's Data Model capabilities, along with maps and geospatial visualization. You will further use Tableau Prep Builder's ability to efficiently clean and structure data. By the end of this audiobook, you will be proficient in implementing the powerful features of Tableau 2022 to improve the business intelligence insights you can extract from your data. Audience This Tableau audiobook is for aspiring BI developers and data analysts, data scientists, researchers, and anyone else who wants to gain a deeper understanding of data through Tableau. This audiobook starts from the ground up, so you won't need any prior experience with Tableau before you dive in, but a full Tableau license (or 14-day demo license) is essential to be able to make use of all the exercises.